2018
DOI: 10.1002/jcb.27778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HMGA2 gene downregulation by siRNA on lung carcinoma cell migration in A549 cell lines

Abstract: Background Although there are multiple treatments for lung cancer, the death rate of this cancer remains high because of metastasis in earlier stages. So a novel treatment for overcoming metastasis is urgently needed. Overexpression of high‐mobility group AT‐hook 2 (HMGA2), a nonhistone chromosomal protein has been observed in metastatic cancers. So, we suggested that HMGA2 upregulation may play a critical role in treating lung cancer. Methods The A549 cells were transfected with specific HMGA2 small interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(190 reference statements)
1
9
0
Order By: Relevance
“…Looking at the results of cell viability assay, we find that G4/MTX containing HMGA2 siRNA is a more effective treatment to reduce cell viability than other treatment groups, which maybe a result of the synergistic effect of two therapeutic agents (MTX and HMGA2 specific siRNA) on cancer cells via efficiently exerting cell death in complementary pathways. In agreement with our study, Naghizadeh et al concluded that, following the use of siRNA against HMGA2, cell proliferation is significantly inhibited [ 42 ]. Apoptosis is a fundamental process that occurs in multicellular organisms in order to eliminate abnormal or unsensational cells and is responsible for different biological functions [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Looking at the results of cell viability assay, we find that G4/MTX containing HMGA2 siRNA is a more effective treatment to reduce cell viability than other treatment groups, which maybe a result of the synergistic effect of two therapeutic agents (MTX and HMGA2 specific siRNA) on cancer cells via efficiently exerting cell death in complementary pathways. In agreement with our study, Naghizadeh et al concluded that, following the use of siRNA against HMGA2, cell proliferation is significantly inhibited [ 42 ]. Apoptosis is a fundamental process that occurs in multicellular organisms in order to eliminate abnormal or unsensational cells and is responsible for different biological functions [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, HMGA2 level is an independent biomarker of NSCLC prognosis [29]. Functionally, HMGA2 has been confirmed as an oncogene during NSCLC initiation and progression [30][31][32]. Here, we proved that HMGA2 expression is positively regulated by VPS9D1-AS1 in NSCLC; further, we showed that this regulatory effect is essential for the tumorigenic actions of VPS9D1-AS1 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 55%
“…The bioinformatics prediction indicated that a site in the 3′-UTR of HMGA2 mRNA matched the "seed sequence" of miR-532-3p ( Figure 4F). HMGA2 was selected for further verification because that this gene was reported to be overexpressed in NSCLC and exert crucial roles during NSCLC initation and progression [29][30][31][32]. A luciferase reporter assay was then performed to demonstrate the possibility of miR-532-3p binding to the 3′-UTR of HMGA2 mRNA in NSCLC cells.…”
Section: Hmga2 Is a Direct Target Gene Of Mir-532-3p In Nsclc Cellsmentioning
confidence: 99%
“…Our research in the present study addresses the potential of a novel therapeutic approach combining a lipid and hydrophobically modified let-7b miRNA that can be useful to target NSCLC with silencing of HMGA2 mRNA. Indeed, the presence of high levels of HMGA2 mRNA has been observed with lung cancer 2 , 5 , 6 , 58 , 59…”
Section: Discussionmentioning
confidence: 99%
“…let-7 encodes a microRNA (miRNA) that targets HMGA2 in lung cancer 1, 2, 3, 4, 5, 6. Lung cancer is responsible for the most cancer-related deaths for both men and women in the US with an estimated 224,390 new cases and 158,080 deaths from the disease in 2016 7 .…”
Section: Introductionmentioning
confidence: 99%